Consent as a Success Factor - The Impact of Cookie Banner Tonality and Regulatory Fit - Sarah Kutscher; Isabelle Kes; Alexander Eiting; Eva Anderl (Marketing Review St.Gallen, 2022)
This paper analyzes the impact of cookie banner tonality and its fit with the consumer's mindset on the intention to give consent. By providing a link between consumer mindsets and cookie banner tonality, this study offers practical guidance regarding the phrasing of cookie banner messages.
Keywords: 650